The impact of thyroid hormone concentration fluctuations on colon cancer proliferation and growth - Ren, Fang; Zhang, Yaqi; Hui, Cancan; Li, Zekai; Deng, Datong (Frontiers in Endocrinology, 2025)
BackgroundTo examine the effects of thyroid hormone (TH) levels on colon cancer progression, HCT-116 colon cancer cells were inoculated into the axillary region of thymus-deficient male BALB/c nude mice. Mild hypothyroidism and hyperthyroidism were then induced to observe tumor growth patterns under different TH conditions.MethodsFollowing subcutaneous tumor implantation, mice were randomly divided into three groups: hyperthyroid (levothyroxine-treated), hypothyroid (methimazole-treated), and control (saline-treated). Tumor volume and final mass were monitored throughout the study period. Excised tumors were subjected to histological analysis including hematoxylin-eosin (HE) staining, immunofluorescence, and TUNEL assay for apoptosis detection.ResultsIn the tumor-bearing experiment conducted with nude mice, the growth curve and tumor weight of the methimazole group exhibited a inhibitory trend compared to the saline group (P<0.05). In the immunofluorescence staining experiment, Ki67 expression was higher in control and hyperthyroid groups than hypothyroid (P<0.01 and P<0.001, respectively), with no significant control-hyperthyroid difference (P>0.05). TUNEL staining results demonstrated no significant presence of TUNEL-positive cells in the subcutaneous tumor tissue of the control group. Additionally, the proportion of TUNEL-positive cells in the subcutaneous tumor tissue of the levothyroxine group was slightly lower than in the control group. (P>0.05), whereas the proportion of TUNEL-positive cells in the methimazole group increased significantly (P<0.0001).ConclusionFluctuations in thyroid hormone levels in the body can affect the proliferation and growth of colon cancer cells. Furthermore, reducing thyroid hormone levels can inhibit the proliferation of colon cancer cells while promoting their apoptosis.